The social determinants of adolescent anxiety and depression in peri-urban South Africa. - Laura Rossouw; Kathryn Watt; Leslie L Davidson; Chris Desmond (PLOS Mental Health, 2024)
The environment in which adolescents live impacts their mental health, through social determinants. We examine the impact of social determinants on anxiety, and depression in adolescents (aged 13-19) in peri-urban KwaZulu-Natal, South Africa. Using structural equation modelling, we identify direct relationships between social determinants and depression/anxiety, as well as indirect pathways between social determinants. Our findings indicate that living with the biological mother, the perception of family and peer support, school enrolment, and a positive sense of school membership may protect adolescent's mental health. Conversely, exposure to community violence may be directly detrimental to adolescent mental health and indirectly harm mental health through the negation of a sense of school membership. Understanding the potential direct and indirect pathways between social determinants and adolescents' mental health in resource-constrained contexts can inform interventions to protect young people's well-being through the identification of appropriate entry points closer to and further from the adolescent and their household.